National picture of the world in O. Bokeev’s prose (Eurasian Journal of Philology Science and Education, 2016)
Currently in different branches of science such concepts-phrases as «the world image», «vision of the world», «national picture of the world» are widely used. These concepts and the related problems of cultural science and philology are especially actual and significant. In the present scientific article the reflection of the national picture of the world in O. Bokeev’s works is considered. Along with it the article gives the information on the origin, history and the use of the term «world picture». In the article with the purpose of specifying the national picture of the world such stories of O. Bokeev as «Man-deer «, «Bura», « The orphaned colt» are taken as examples. The writer, using images-symbols, skillfully represented the national mentality of the Kazakh people. The writer by means of such images showed the originality of the national outlook of Kazakhs in the works.
Keywords: world picture; national picture of the world; national originality; character; image; symbol; traditions.